Tinjauan Komprehensif Evolusi, Aplikasi, dan Tren Masa Depan Programmable Logic Controllers (A Comprehensive Review of the Evolution, Applications, and Future Trends of Programmable Logic Controllers) - Herdiana, Budi; Setiawan, Eko Budi; Sartoyo, Usman (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2023)
Programmable Logic Controllers (PLCs) have become indispensable components in industrial automation and control systems since their inception. The rapid advancement of PLCs has necessitated a comprehensive review of their applications across diverse industries. This article presents a holistic overview of PLCs, encompassing their varied applications, evolutionary development, and future trends. A comprehensive literature review was conducted, gathering and analyzing information from credible sources, including scientific journals, textbooks, and industry reports. The findings reveal that PLCs have been extensively implemented across a wide spectrum of industries, including manufacturing, energy, water treatment, transportation, building automation, and agriculture. The integration of technologies such as the Internet of Things (IoT), artificial intelligence (AI), and cybersecurity measures has enhanced the functionality and security of PLC systems. Case studies presented in this article demonstrate the practical implementation and benefits of PLCs in various real-world scenarios. PLCs have been proven to play a pivotal role in improving operational efficiency, reliability, and productivity across diverse sectors. Challenges and future trends discussed in this article include PLC integration in Industry 4.0 and intelligent automation. The conclusion of this review is that PLCs are an essential automation technology with wide-ranging applications across industries. Continuous research and development efforts are crucial to optimize PLC technology and its applications in the future.